Manajemen Strategi Pengembangan Akademik dan Budaya Perguruan Tinggi Islam Di Indonesia : Inovasi Menuju Karakter Ulul Albab - Zainal Abidin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Abstract: Implementation of Learning of The Akidah Akhlak In The Character of Loving The Country.The strategy for developing an academic culture can create students who have a sense of eco-spirituality in interacting with nature. This study aims to examine the strategy for developing the academic culture and religious character of Ulul Albab which produces graduates of Indonesian Islamic Universities with a case study at Fatmawati Sukarno Bengkulu State Islamic University. Qualitative research methods are applied to conduct research. The results of the research show that the strategy for developing academic and religious culture can be built through: 1) Integration of religion and science; 2) Integration of Universities and Ma'had/boarding schools; 3) Orientation for the formation of Ulul Albab; 4) Setting standards for the success of Ulul Albab Bachelors; 5) Setting goals and commitments; 6) Building a fasting culture; 7) Open, mutual dialogue and advice; 8) Oriented to equality and togetherness; 9) appropriate and strong leadership through spiritual, emotional, intellectual, and social approaches; 10) Developing a culture of writing and research; and 11) Creating new innovations continuously. The research finding model is a strategy for developing academic and religious culture in Islamic tertiary institutions in Indonesia to produce graduates with Ulul Albab Character.Abstrak: Manajemen Strategi Pengembangan Akademik dan Budaya Perguruan Tinggi Islam Di Indonesia : Inovasi Menuju Karakter Ulul Albab.Strategi pengembangan budaya akademik dapat menciptakan mahasiswa yang memiliki rasa eco-spirituality dalam berinteraksi dengan alam. Penelitian ini bertujuan untuk mengkaji strategi pengembangan budaya akademik dan karakter religius Ulul Albab yang menghasilkan lulusan Perguruan Tinggi Islam Indonesia dengan studi kasus di Universitas Islam Negeri Fatmawati Sukarno Bengkulu. Metode penelitian kualitatif diterapkan untuk melakukan penelitian. Hasil penelitian menunjukkan bahwa strategi pengembangan budaya akademik dan keagamaan dapat dibangun melalui: 1) Integrasi agama dan ilmu pengetahuan; 2) Integrasi Perguruan Tinggi dan Ma'had/pondok; 3) Orientasi pembentukan Ulul Albab; 4) Menetapkan standar keberhasilan Sarjana Ulul Albab; 5) Menetapkan tujuan dan komitmen; 6) Membangun budaya puasa; 7) Terbuka, dialog timbal balik dan nasihat; 8) Berorientasi kesamaan dan kebersamaan; 9) kepemimpinan yang tepat dan kuat melalui pendekatan spiritual, emosional, intelektual, dan sosial; 10) Mengembangkan budaya menulis dan meneliti; dan 11) Menciptakan inovasi baru secara terus menerus. Model temuan penelitian adalah strategi pengembangan akademik dan budaya keagamaan di perguruan tinggi Islam di Indonesia untuk melahirkan lulusan yang berkarakter Ulul Albab.